2015
DOI: 10.7324/japs.2015.50906
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents of Cycas aenigma

Abstract: Chemical investigation of Cycas aenigma, a plant endemic to the Philippines, led to the isolation of a rare neolignan, 2-[2-hydroxy-5-(3-hydroxypropyl)-3-methoxyphenyl]-1-(4-hydroxy-3-methoxyphenyl)propane-1,3-diol (1), pinoresinol (2), and fatty alcohols (3) from the leaflets; and triglycerols (4), and a mixture of β-sitosterol (5a) and stigmasterol (5b) from the petiole and rachis. The structure of 1 was elucidated by extensive 1D and 2D NMR spectroscopy, while those of 2-5b were identified by comparison of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…Silica gel chromatography of the dichlorometnahe extract of the leaves of P. nauseosa afforded squalene (1), βsitosterol (2) and stigmasterol (3). The NMR spectra of 1 are in accordance with data reported in the literature for squalene 3 ; 2 for β-sitosterol 4 ; and 3 for stigmasterol 4 4 . Although no biological tests were conducted on the isolated compounds, a literature search of 1-3 revealed that these have diverse bioactivities.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Silica gel chromatography of the dichlorometnahe extract of the leaves of P. nauseosa afforded squalene (1), βsitosterol (2) and stigmasterol (3). The NMR spectra of 1 are in accordance with data reported in the literature for squalene 3 ; 2 for β-sitosterol 4 ; and 3 for stigmasterol 4 4 . Although no biological tests were conducted on the isolated compounds, a literature search of 1-3 revealed that these have diverse bioactivities.…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, the ethanolic extract possessed 78% free radical scavenging activity based on DPPH assay 2 . In this study, the dichloromethane extract of P. nauseosa leaves yielded squalene (1) and a mixture of β-sitosterol (2) and stigmasterol (3). The structures of 1-3 are presented in Fig.…”
Section: Introductionmentioning
confidence: 79%
“…Silica gel chromatography of the dichloromethane extracts of D. dao yielded 1-11. The NMR spectra of 1 are in accordance with data reported in the literature forcardanol; 7 2 for βsitosteryl3βglucopyranoside6' Ofatty acid esters; 8 3 for βsitosteryl fatty acid ester; 9 4a for βsitosterol; 10 4b for stigmasterol; 10 5 for anacardic acid; 11 6 for triacylglycerols; 12 7 for monoacylglycerol; 10 8 for longchain fatty acid esters; 13 9 for linoleic acid; 14 10 for longchain fatty alcohols; 15 and 11 for longchain hydro carbons. 16…”
Section: Resultssupporting
confidence: 85%
“…The structure of β-friedelinol (1) was elucidated by extensive 1D and 2D NMR spectroscopy and confirmed by comparison of its NMR data with those reported in the literature for β-friedelinol [7]. The NMR spectra of lupeol (2) are in accordance with data reported in the literature for lupeol [8]; squalene (3) for squalene [9]; polyprenol (4) for polyprenol [10]; β-sitosterol (5) for βsitosterol [11]; long-chain hydrocarbons (6) for long-chain hydrocarbons [12]; chlorophyll-a (7) for chlorophyll-a [13] and triacylglycerols (8) for triacylglycerols [14].…”
Section: Isolation Of Chemical Constituents From Leaves Of a A Ghaesupporting
confidence: 83%